A Cognitive Stylistic Analysis of Kofi Awoonor's The Weaver Bird - Cynthia Ma; Nikita Tantira; Delfi Nazilah Lubis; Theofani Leonita Siagian; Rahmadsyah Rangkuti (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
Colonial trauma has left a lasting imprint on postcolonial literature, shaping narratives of displacement, resistance, and cultural transformation. This study examines Kofi Awoonor's The Weaver Bird using a cognitive stylistic approach to uncover the mental processes influencing readers' perceptions of colonialism. African poetry remains underexplored in cognitive stylistics, making this study significant in broadening the scope of literary analysis. By integrating Conceptual Metaphor Theory and Conceptual Blending Theory, this research explores how Awoonor's language constructs an embodied experience of loss and perseverance. Employing a qualitative method, the study conducts a close textual analysis to identify cognitive mechanisms shaping meaning in the poem. Findings reveal that metaphorical structures trigger cognitive processes that reinforce postcolonial awareness and collective identity. This study contributes to both literary and psychological research by demonstrating how poetry functions as a cognitive tool in processing historical realities. Its implications suggest that literature is not merely a reflection of history but an active force in shaping thought, memory, and resistance.